Hydroxyapatite nano-rods for the fast removal of congo red dye from aqueous solution. (27th June 2018) - Guan, Yebin; Cao, Weicheng; Wang, Xiaohong; Marchetti, Alessandro; Tu, Youzhi
Abstract: Adsorption rate is one of the key indicators to evaluate the adsorption performance of a nanomaterial. Herein, nanosized rod-like HAP particles were prepared via a facile hydrothermal process by using guanidine phosphate as the phosphorus source. HAP nanoparticles show a rough surface and a high BET surface area (82.94 m 2 g −1 ), and display an excellent adsorption rate for the removal of congo red (CR) dye in aqueous solution with a maximum adsorption capacity of 337.330 mg g −1 . Thus, this kind of HAP nanoparticles can be used as an efficient, fast and low-cost adsorbent for the treatment of industrial effluents contaminated with similar anionic dyes.